Efficiency of occlusal splints on police officers with TMD - Caria, Paulo Henrique Ferreira; Faria, Reinaldo José A.; Faria, Claudia Regina Sgobbi De [UNESP]; Croci, Carla Scanavini; Negrão Filho, Rubens [UNESP] (Faculdade de Odontologia de Piracicaba - UNICAMP, 2014)
Aim: To evaluate of the effect of two different occlusal splints on police officers with TMD. Methods: Thirty police officers were selected based on Research Diagnostic Criteria for TMD and on clinical exams. Volunteers (ten per group) were distributed according to occlusal splints: group A - Control, group B - Michigan Occlusal Splint (MOS), and group C - Planas Appliance (PA). Experimental groups were analyzed using a visual analog pain scale (VAPS), subject to a clinical evaluation of temporomandibular joint. Bilateral surface electromyographic activities of anterior and posterior temporal, masseter and suprahyoid muscles were analyzed at rest and during clenching, before and after four weeks using the occlusal splints. Results: The left and right temporal and masseter muscles sensitivity decreased after using both splints. Pain symptoms increased for group A (Control) and decreased for group C. Conclusions: Planas Appliance was more efficient on pain reduction than the Michigan Occlusal Splint.
Keywords: Temporomandibular joint disorders; Stress physiological; Electromyography, masticatory muscles, occlusal splints